Clinical differences between cocaine-dependent patients with and without antisocial personality disorder. (30th December 2016) - Comín, Marina; Redondo, Santiago; Daigre, Constanza; Grau-López, Lara; Casas, Miguel; Roncero, Carlos
Abstract: The aim of this study is to compare the features of two groups of cocaine dependent patients in treatment, one of them with co-morbid diagnosis of antisocial personality disorder and the other not. Cross-sectional design, with 143 cocaine-dependent patients attending a drug unit, distributed in two groups: patients with and without Antisocial Personality Disorder. As results, we found that the 15.38% of the sample were diagnosed with an Antisocial Personality Disorder. In relation to socio-demographic variables, Antisocial Personality Disorder patients have less probability of being working or studying (9.1% vs. 47.9%). After multivariate analysis it was found that significantly Antisocial Personality Disorder patients have more opiates dependence (OR: 0.219; 95% IC 0.072–0.660), sedative dependence (OR: 0.203; 95% IC 0.062–0.644) and in more cases show Borderline Personality Disorder (OR: 0.239; 95% IC 0.077–0.746). This study highlights significant differences between cocaine addicts with or without an Antisocial Personality Disorder. All these differences are good indicators of the complexity of the patients with this personality disorder. Better knowledge of their profile will help us to improve the design of specific treatment programs. Highlights: Treating patients a Cocaine Dependence co-morbid with an Antisocial Personality Disorder is a complex issue. There is limited evidence of the effectiveness of commonly used psychotropic drugs. Better assessment and knowledge of individual differences and characteristics of these people, could have important implications for adjusting and improving future treatment programs and to prevent worsening their condition and quality of life.